Evaluation The Effectivity Of Performance Management Online System To Improving The Employees Performance - I Gusti Putu Anom Artawijaya; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2015)
The result of this research showed that, there is a positive relationship betweenvariables The Capability of Performance Management System and The Capability ofTechnology to the variables The Effectivity of Performance Assessment and also there is apositive relationship between variables Leadership Involvement/Manager and The Effectivityof Performance Assessment to thevariables Employee Performance.On the other hand, the variables of Leadership Involvement/Manager have nosignificant relationship to the variables The Effectivity of Performance Assessment and alsothe variables The Capability of Performance Management have no significant relationshipdirectly to the variables Employee Performance.Key words: Leadership Involvement/Manager, The Capability of PerformanceManagement System, The Capability of Technology, The Effectivity of PerformanceAssessment and Employee Performance.